Women Leadership in the Arab World - Ladki, Said (2010)
This paper explores the phenomenon of leadership with the intent to improve the practice, to understand, and to influence people while focusing on gender issues. Queen Rania Al Abdullah, the Queen of Jordan, presents a substantial representation of effective women in power, an inspiration to all women, and most importantly a Female Leader in the Arab World. The paper analyzes the Queen’s practices to reveal how concepts and ideas of leadership can be shaped and applied in societal reality. The absence of leadership is often seen as an absence of organization. Leadership’s concepts, practices and variant forms of direction and control are so powerfully ingrained into popular thoughts. Such thoughts shape today’s dynamics, frame of work, and decision making. Communities are paralyzed by situations in which people appeal for direction. Not being led causes people to feel immobilized and disorganized. Successful acts of leadership are often seen as the synchrony between the initiation of action and the appeal for direction (Pierce and Newstrom, 2007). It is assumed that the actions of leaders along with the openness and responsiveness of followers results in successful leadership. This paper explores the phenomenon of leadership with the intent to improve the practice, to understand, and to influence people while focusing on gender issues. “Leadership and related phenomena such as power, authority, and influence has been the subject of much theorizing and research” (Suyemoto, 2008).